Reconfiguração dinâmica de uma linha robótica de modelo misto com impacto reduzido no tempo de ciclo - Baeta, Claudio Luiz Faria (2021)
The Industry 4.0 and flexible on-demand production concepts have introduced assembly lines in the automotive industry subject to constant changes in demand and vehicle models (mixed-model line). Based on a literature model for the optimized design of mixed-model robotic assembly lines, this work implements a simulation model of the line considered under different operating conditions. Idle stations are identified and part of the robots is disabled. The results show that it is possible to reconfigure the line as different vehicle models are produced, disabling robots from certain stations. Furthermore, the cycle time is not altered or changed slightly when disabling robots. Scenarios with relevant impact on the cycle time with the production of a “mix” of vehicle models and different vehicle sequences are also considered. These results can be used for scheduled robots maintenance or less utilization of robots.